2015
DOI: 10.3746/pnf.2015.20.3.183
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Egg White Liquid Hydrolysate (ELH) and Its Radical-Scavenging Activity

Abstract: In the present study, an optimum protease was selected to hydrolyze the egg white liquid protein for the antioxidant peptides. Alcalase treatment yielded the highest amount of -amino groups (15.27 mg/mL), while the control (no enzymatic hydrolysis) showed the lowest amount of -amino groups (1.53 mg/mL). Alcalase also gave the highest degree of hydrolysis (DH) value (43.2%) and was more efficient for egg white liquid hydrolysis than the other enzymes. The Alcalase hydrolysate had the highest radical-scavengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Similar results using the same hydrolysis protocol were reported later proving that antioxidant activity of peptides is intimately connected to their molecular weight [57]. Furthermore, other studies have also reported increased antioxidant activity of egg white hydrolysate with alcalase, although using different hydrolysis conditions [43,[67][68][69].…”
Section: Hydrolysis Of Egg Whitesupporting
confidence: 82%
“…Similar results using the same hydrolysis protocol were reported later proving that antioxidant activity of peptides is intimately connected to their molecular weight [57]. Furthermore, other studies have also reported increased antioxidant activity of egg white hydrolysate with alcalase, although using different hydrolysis conditions [43,[67][68][69].…”
Section: Hydrolysis Of Egg Whitesupporting
confidence: 82%
“…The amino acid mixture used in the present study contained these amino acids, and thus they also would exert the strongest effect under acidic conditions. As described previously, some studies 11,34,35,40) reported that hydrolysate exhibited stronger inhibitory effects than the parental proteins on lipid oxidation and that the DPPH radical-scavenging activity of the hydrolysate was one of the mechanisms responsible for the stronger antioxidative effect. Egg white hydrolysate also displayed DPPH radical-scavenging activity.…”
Section: Discussionmentioning
confidence: 75%
“…A high DH corresponds to more peptide production and is often related to high bioactivity. For instance, Noh and Suh [31] who hydrolyzed egg white liquid using Alcalase, Neutrase, Protamex, Flavourzyme, Collupulin and Ficin had reported a positive correlation between DH and antioxidant activity. Alcalase hydrolysate produced at S/E 50 w/w and 24 h recorded the highest DH (43.2%) and free radical scavenging effects (82.5%) compared to other enzyme treatments.…”
Section: Single-factor Experimentsmentioning
confidence: 99%